2021
DOI: 10.1093/plphys/kiab444
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for glutathione transferase U7 in plant growth and protection from methyl viologen-induced oxidative stress

Abstract: Plant glutathione S-transferases (GSTs) are glutathione-dependent enzymes with versatile functions, mainly related to detoxification of electrophilic xenobiotics and peroxides. The Arabidopsis (Arabidopsis thaliana) genome codes for 53 GSTs, divided into seven subclasses, however, understanding of their precise functions is limited. A recent study showed that class II TGA transcription factors TGA2, TGA5 and TGA6 are essential for tolerance of UV-B-induced oxidative stress and that this tolerance is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 108 publications
5
20
0
Order By: Relevance
“…PtGSTF1 was abundantly expressed in leaves and was responsive to high salt stress ( Figure 1 b,c). This is similar to the expression patterns of other previously reported GST members, which showed induced expression by various biotic and abiotic stresses in different biological metabolism processes [ 16 , 31 , 33 , 34 , 44 , 45 ]. In Arabidopsis, GSTU7 was reported to be localized in the cytosol, whereas the tea CsGSTU8 was found to be distributed throughout the cell [ 16 , 17 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…PtGSTF1 was abundantly expressed in leaves and was responsive to high salt stress ( Figure 1 b,c). This is similar to the expression patterns of other previously reported GST members, which showed induced expression by various biotic and abiotic stresses in different biological metabolism processes [ 16 , 31 , 33 , 34 , 44 , 45 ]. In Arabidopsis, GSTU7 was reported to be localized in the cytosol, whereas the tea CsGSTU8 was found to be distributed throughout the cell [ 16 , 17 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to the expression patterns of other previously reported GST members, which showed induced expression by various biotic and abiotic stresses in different biological metabolism processes [ 16 , 31 , 33 , 34 , 44 , 45 ]. In Arabidopsis, GSTU7 was reported to be localized in the cytosol, whereas the tea CsGSTU8 was found to be distributed throughout the cell [ 16 , 17 , 46 , 47 ]. We observed that PtGSTF1 was located in the cytoplasm, implying that it may have a similar role to the GSTU7 protein ( Figure 1 c).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations